Virulence of Trypanosoma cruzi Strains Is Related to the Differential Expression of Innate Immune Receptors in the Heart - Queiroga, Tamyres Bernadete Dantas; Pereira, Nathalie de Sena; Silva, Denis Dantas da; Andrade, Cléber de Mesquita; Araújo Júnior, Raimundo Fernandes de; Brito, Carlos Ramon do Nascimento; Galvão, Lúcia Maria da Cunha; Câmara, Antônia Cláudia Jácome da; Nascimento, Manuela Sales Lima; Guedes, Paulo Marcos Matta (Frontiers in Cellular and Infection Microbiology, 2021)
Resistance or susceptibility to T. cruzi infection is dependent on the host immunological profile. Innate immune receptors, such as Toll-Like Receptors (TLRs/ TLR2, TLR4, TLR7 and TLR9) and Nod Like Receptors (NLRs/ NOD1 and NLRP3 inflammasome) are involved with the resistance against experimental acute T. cruzi infection. Here, we evaluated the impact of T. cruzi virulence on the expression of innate immune receptors and its products in mice. For that, we used six T. cruzi strains/isolates that shown low (AM64/TcIV and 3253/Tc-V), medium (PL1.10.14/TcIII and CL/TcVI) or high (Colombian/Tc-I and Y/TcII) virulence and pathogenicity to the vertebrate host and belonging to the six discrete typing units (DTUs) – TcI to TcVI. Parasitemia, mortality and myocarditis were evaluated and correlated to the expression of TLRs, NLRs, adapter molecules, cytokines and iNOS in myocardium by Real Time PCR. Cytokines (IL-1β, IL-12, TNF-α and IFN-γ) were quantified in sera 15 days after infection. Our data indicate that high virulent strains of T. cruzi, which generate high parasitemia, severe myocarditis and 100% of mortality in infected mice, inhibit the expression of TLR2, TLR4, TLR9, TRIF and Myd88 transcripts, leading to a low IL-12 production, when compared to medium and low virulent T. cruzi strains. On the other hand, the high virulent T. cruzi strains induce the upregulation of NLRP3, caspase-1, IL-1β, TNF-α and iNOS mRNA in heart muscle, compared to low and medium virulent strains, which may contribute to myocarditis and death. Moreover, high virulent strains induce higher levels of IL-1β and TNF-α in sera compared to less virulent parasites. Altogether the data indicate that differential TLRs and NLRs expression in heart muscle is correlated with virulence and pathogenicity of T cruzi strains. A better knowledge of the immunological mechanisms involved in resistance to T. cruzi infection is important to understand the natural history of Chagas disease, can lead to identification of immunological markers and/or to serve as a basis for alternative therapies.